Enhancing Employee Retention Through the Moderating Effects of Organizational Justice and Work–Life Balance Among Employees of Three-Star Hotels in Pontianak City - Ginting, Sunardi (LPPM ISNJ Bengkalis, 2025)
This study examines the effect of role conflict on employee retention, moderated by organizational justice and work-life balance, based on data collected from 250 randomly selected respondents from 14 three-star hotels in Pontianak City. Based on the average responses, it can be concluded that the participants experienced a high level of role conflict, held positive perceptions of organizational justice and work-life balance, and also reported high levels of retention. Overall, the hypotheses of this study are supported. Role conflict is found to be a significant negative predictor of employee retention, while organizational justice and work-life balance are significant positive predictors. Regarding the moderating effects, both moderating variables significantly influence the relationship between role conflict and employee retention. Specifically, organizational justice weakens the negative impact of role conflict on employee retention, whereas work-life balance unexpectedly strengthens the negative effect of role conflict on retention. When the direct and moderating effects were examined at the indicator level, only 2 out of 4 indicators of organizational justice and 3 out of 4 indicators of work-life balance were found to be significant predictors of employee retention. Furthermore, only 3 out of 4 organizational justice indicators and 1 out of 4 work-life balance indicators significantly moderated the relationship between role conflict and employee retention. Among the indicators tested, informational justice and interference of personal life with work emerged as the strongest predictors of employee retention. To improve the quality of future research, it is recommended to conduct analyses based on generational cohorts, as each generation tends to hold different perspectives regarding the variables examined in this study.